Relationship between vessel parameters and cleavage associated with checking in eucalyptus grandis wood - Charles Dias Soares, Bruno; Tarcísio Lima, José; Reinaldo Moreira da Silva, José (Maderas. Ciencia y Tecnología, 2021)
In this work, the relationship between vessels parameters and the wood cleavage strength were studied to clarify the process of formation of this type of check, very common in Eucalyptus wood. The objective was to identify the relationship between the wood cleavage strength, the average area of the vessel, and the percentage area of vessels on the wood transverse surface. For this, two Eucalyptus grandis trees at 22 years old were felled and specimens for the cleavage test were produced to determine the wood cleavage strength. From these specimens, samples were taken to determine the average area of the vessel and the percentage area of vessels, aiming at adjusting mathematical models that explain the variation in the cleavage strength. The results showed that the higher the average area of the vessel and the percentage of area occupied by vessels in the wood, the lower its cleavage strength. The multiple linear regression model can estimate the cleavage strength as a function of the average area of the vessel, and the percentage area of the vessels.